Tiger taming - Sykes, Julie; Reed, Nathan (New York Kingfisher, 2009)
When animal lover Max sets up a pet-sitting business, he finds himself looking after some very unusual pets. Max can't wait to take care of Miss Warble Itchy's black cat, Tiger. But a witch's cat can really be a handful-- talking back, drinking forbidden bat juice, and getting kidnapped by an angry wizard.
97265
Keywords: Pet sitting; Cats; Magic; Witches; Children's stories